Generic assumption-based truth-maintained blackboard system - Tan, Boon Tee. (2008)
Problem solving involves making a sequence of decisions under a set of constraints that satisfies the required goal. Typically, a computational problem solver relies on search to explore the different possibilities to solve a problem. The control problem in a problem solver is the task of selecting the best action to execute that brings the state of the solution closer to the required goal.